ANALISIS STABILITAS LERENG DENGAN KONTRUKSI DINDING PENAHAN TANAH TIPE COUNTERFORT - Karsa Ciptaning; Yuhanis Yunus; Sofyan M. Saleh (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2018)
The Babahrot - Blangkejeren road of a segment is one of the most frequently affected by a landslide due to its location in the range of hills in Aceh Province. The road is the only one facilities to connect between both cities, and it is the only one to access for crop trading as well other plantation. The impact of landslide causes disconnection from Gayo Lues to South West Aceh or vice versa. Therefore, it is necessary to study the slope reinforcement at the bottom of the road construction with retaining wall counterfort type.  This study aims to analyze slope stability by obtaining reasonable Safety Factor (SF). The method used is Fellenius Method and combining modeling using the Geoslope software. The Fellenius calculation employed static seismic load. Meanwhile, the Geoslope Program utilized either with or without static seismic load.  The static analysis was carried out based on Indonesian Seismic Zone map (2004) for 50 years (coefficient 0.229). The scope of the analysis was a calculation of slope stability includes calculating slope stability on STA 13 + 885. The result of slope stability analysis on the existing using gdry and gwet with the Geo Slope software both without and by using static seismic load on STA 13+885 is unsafe. Thus, handling the existing is needed. The counterfort of retaining wall is considered to use for alternative slope stability construction. The result of slope stability analysis using Counterfort has safety factor greater than 1,5, if additional handling is done by changing slope angle lower than 20°.